Psicanalisi, educazione speciale e formazione di insegnanti. La costruzione del caso come dispositivo di inclusione scolastica - Moschen, Simone; Vasques, Carla; Simiano, Luciane (Studi sulla Formazione/Open Journal of Education, 2015)
The text studies the special education in Brazil and describes an experience about a continuing education course addressed to teachers that work with children and made by researchers of differ field of knowledge (pedagogy, psychology, philoso- phy and psychoanalysis).